Groundwater quality in the Valigamam region of the Jaffna Peninsula, Sri Lanka - Rajasooriyar, L.D.; Mathavan, V.; Dharmagunawardhane, H.A.; Nandakumar, V. (University of St Andrews, 2015)
The Valigamam region is underlain by a Miocene limestone formation and a highly porous soil cover. The region is totally dependent on groundwater to meet its agricultural, industrial and domestic needs, since other sources of water are seasonal. Recharge from rainfall is limited by high run-off and evapotranspirational losses. The region experiences water supply problems due to high concentrations of chloride, total hardness and nitrate in groundwater. The spatial distribution of chloride varies from year to year, with maximum concentrations experienced during or after the wet season. The major factor explaining high chloride concentrations is the excessive extraction of groundwater that results in saline intrusion from the sea or tagoonal areas. In a large proportion of wells sampled for nitrate, levels exceed the WHO standard due to intensive agricultural practices involving very high inputs of artificial and natural fertilizers and the improper construction of latrine soakaway pits. To improve groundwater quality in the Jaffna Peninsula will require controls on the location of new wells, a revision of existing and future pumping rates and a change in agricultural practices. It is imperative that future work in the region should focus on combining groundwater management and sustainable agricultural practice.